Perfil sociodemográfico da formação profissional e do trabalho dos médicos que atuam em cuidados paliativos no Brasil - Mendes, Priscilla Biazibetti (2021)
Palliative Care is the multidisciplinary healthcare model that seeks to provide the comfort of patients who have a life-threatening disease. Objectives: To outline the profile of the doctor who works in Palliative Care in Brazil; identify your sociodemographic profile; their professional background and their current work activity. Methods: This is Survey-type research, cross-sectional, descriptive and exploratory, with a quantitative approach. An online questionnaire was applied to physicians working in Palliative Care in Brazil, with or without a proven field of expertise. Results: A total of 163 physicians participated in the study, most of them female (71.8%), aged between 30 and 49 years (77.9%), married (76.7%), living in the Southeast region of the country (60.7%), with remuneration like the average salary of doctors in the country. Most physicians completed the medical course after the 2000s (72.2%), graduated from public schools (54%). The most frequent medical specialties performed by the participants were: Internal Medicine (39.4%), Geriatrics (21.7%), Family and Community Medicine (8.4%). A total of 75.5% of the participants have a proven field of expertise in Palliative Medicine, with the largest portion obtaining the title through proof of sufficiency title (62.6%). Only 11.7% of the participants decided to work with Palliative Care during medical graduation, with a tendency to decide to work in the area during specialization or residency in other medical areas. It was observed that most of the population studied had less than 10 years of work experience in Palliative Care (72.2%). In professional practice in the area, 83.6% of physicians have a multidisciplinary support team. Only 22.4% of participants work exclusively in Palliative Medicine. Participants reported that they work at different levels of care, with the hospital level being predominant. A total of 76.7% of physicians work in some teaching activity in Palliative Care. Personal satisfaction and the desire to take care of the other were the main reasons cited for these professionals to work in the area. Regarding the degree of personal satisfaction, no participant responded that they were "very satisfied" in working as a palliative doctor, 59.8% considered themselves "satisfied" and 38.8% said they were "not very satisfied". working with palliative care has some impact on their mental health (85.7%) Conclusion: Palliative Medicine is an area of medical activity recently recognized in the country, being essential the detailed knowledge of the doctor who works in this area. of teaching in palliative care in medical education, especially during graduation; expanding access for physicians with more specialties to obtain the title of area of expertise in palliative medicine and seeking a favorable working environment for physicians in palliative services, with adequate technical resources and focused on their psychological integrity, can be important points in the consolidation of this new area of activity in the country. Studies that detail the professional's satisfaction in working in palliative care are relevant to this context.